Respect for personal autonomy in AI regulatory framework - Sukhorolskyi, Petro (Problems of legality, 2025)
The legal regulation of artificial intelligence is one of the most pressing and debated topics at the national and international levels. The rapid development of artificial intelligence can significantly change the existing reality and leads to fundamentally new challenges for lawmaking and law enforcement, in particular in the field of human rights. The main purpose of the article is to determine whether the new European legal instruments on artificial intelligence (in particular, the European Union’s AI Act and the Council of Europe’s Framework Convention on AI) reflect these technological threats and protect the personal autonomy of individuals. To achieve this goal, the article reveals the essence of personal autonomy and its significance for human rights and the legal system, as well as identifies the directions of the real and potential impact of artificial intelligence on personal autonomy. The theoretical and methodological foundation of the study is Joseph Raz’s theory of personal autonomy which allows to identify the main problems and contradictions in the use of artificial intelligence and to shape proposals for responding to actual threats. Based on the idea of the fundamental role of personal autonomy, the article shows how the introduction of artificial intelligence, driven by the interests of specific actors, negatively affects the position, rights and capacities of individuals. In particular, the author identifies three directions of such influence: high-tech manipulation of people, distortion of their perception through myths and misconceptions, and formation of the appropriate online architecture and social norms. Based on the analysis of legal documents, two approaches to the regulation of artificial intelligence are identified. The first approach relegates personal autonomy to the periphery and suggests that problems should be solved through cooperation between government and business by using risk assessment tools. This should result in ready-made solutions that are offered to people. The second human-centred approach emphasises the protection of personal autonomy. However, detailed norms within this approach have not yet been created, and their development requires further theoretical elaborations. In this regard, the primary focus should be on preserving and improving the conditions of autonomy that are threatened by the misuse of artificial intelligence.